2009
DOI: 10.1007/s11244-009-9359-1
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the Role of Hydrogen in H2-Assisted HC–SCR Over Ag–Al2O3

Abstract: The role of hydrogen in H 2 -assisted HC-SCR of NO x over Ag-Al 2 O 3 is investigated by XPS and in situ DRIFT spectroscopy. Hydrogen does not reduce the surface silver species to metallic silver, however direct reduction of surface nitrates by hydrogen is observed. It is proposed that one important role of hydrogen is the removal of nitrates from the Ag-Al 2 O 3 surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…It can be clearly seen in Figure 4A It has been reported that Ag has lower binding energy with increasing oxidation state due to its core-level photo- The Journal of Physical Chemistry C Article emission. 18,28 According to this empirical rule, supported silver species for all samples are mostly close to the +1 oxidation state, just like Ag + ion in AgNO 3 solid, even though silver metal XRD peaks were found for "150 r/min" and "Al 2 O 3 mill + AgNO 3 mill" samples. Figure 4B shows the Fourier transforms of k 3 -weighted EXAFS oscillations at the Ag K-edge.…”
Section: Resultsmentioning
confidence: 88%
“…It can be clearly seen in Figure 4A It has been reported that Ag has lower binding energy with increasing oxidation state due to its core-level photo- The Journal of Physical Chemistry C Article emission. 18,28 According to this empirical rule, supported silver species for all samples are mostly close to the +1 oxidation state, just like Ag + ion in AgNO 3 solid, even though silver metal XRD peaks were found for "150 r/min" and "Al 2 O 3 mill + AgNO 3 mill" samples. Figure 4B shows the Fourier transforms of k 3 -weighted EXAFS oscillations at the Ag K-edge.…”
Section: Resultsmentioning
confidence: 88%
“…NO and O2 form NOx surface species (nitrates and nitrites). Strongly adsorbed nitrate is known to self-inhibit the NOx reduction at low temperature [22,23]. For activation of HC, the O2 partially oxidizes the HC to form oxygenated HC surface components.…”
Section: Introductionmentioning
confidence: 99%
“…The spectra were recorded between 20 and 80° (2θ). The mean crystallite size (d) of the catalyst was calculated from the line broadening of the most intense reflection using the Scherrer"s formula in Equation (11). (11) where d is the mean crystallite diameter, 0.89 is the Scherrer constant, λ is X-ray wavelength (Cu Kα radiation) = 1.54056 Å, and  is effective line width of the observed X-ray reflection, calculated by the expression  2 =B 2 -b 2 ; where B is full width half maximum (FWHM) and b is instrumental broadening determined through the FWHM of the X-ray reflection at 2θ of crystalline SiO2.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…), precious metal (Ag/Al2O3, Au-Ag/Al2O3) and transition metals (V2O5-WO3/TiO2, Cu-ZSM-5, Fe-ZSM-5, etc.) [7][8][9][10][11][12]. PGM catalysts are highly active but they are costly, low abundance and vulnerable to further price increases with increasing demand.…”
Section: Introductionmentioning
confidence: 99%